2007
DOI: 10.1021/bc060141b
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolythioureas:  A New Non-Cationic System for Gene Transfer

Abstract: A DNA-transfection protocol has been developed that makes use of thiourea non-cationic synthetic lipid, N-[1,3-bis(carbamothioylamino)propan-2-yl]-2-(dialkycarbamoylmethoxy)acetamide. It was found that these new compounds could be formulated without helper lipid and that the N-decanoyl and N-lauryl derivatives transfected B16 cells in the presence of serum with an efficiency at the same level as cationic lipids, under identical conditions. In vivo transfection using intratumoral injection was also investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 32 publications
4
36
0
Order By: Relevance
“…As previously reported [18], the lipid 1a is able to compact DNA at a TU/P ratio of 10. A gel retardation experiment showed that the lipid 1b is also able to compact DNA but requires a TU/P ratio of 40 ( Figure 6).…”
Section: -Physico-chemical Properties and Interaction With Dnasupporting
confidence: 83%
See 4 more Smart Citations
“…As previously reported [18], the lipid 1a is able to compact DNA at a TU/P ratio of 10. A gel retardation experiment showed that the lipid 1b is also able to compact DNA but requires a TU/P ratio of 40 ( Figure 6).…”
Section: -Physico-chemical Properties and Interaction With Dnasupporting
confidence: 83%
“…However, this does not reflect all the mechanisms of interaction between thiourea lipids and DNA as compound 1b which only bears thiourea functions is able to interact with DNA although less efficiently. The compounds from the "lysine" lipopolythiourea family [16][17][18] which are also able to compact DNA do not undergo acidic conditions during their synthesis which implies that DNA compaction does not necessarily need electrostatic interactions. The lysine structure of this family of compounds might induce rigidity in the lipid structure which surely affects the DNA compaction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations